2016
DOI: 10.1080/14783363.2016.1187995
|View full text |Cite
|
Sign up to set email alerts
|

A systematic assessment of quality assurance-based food safety management system of Chinese edible oil manufacturer in view of context characteristics

Abstract: This study uses a framework of a food safety management system-diagnostic instrument (FSMS-DI), for the assessment of the context of a Chinese edible oil manufacture through the view of a case study, and an evaluation of the performance of the FSMS of a Chinese edible oil company. The study includes a structured interview with the quality assurance manager. FSMS-DI is used to diagnose the core control and assurance activities, as well as the riskiness of context factors and output of the system. A factory tour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 34 publications
0
10
0
1
Order By: Relevance
“…There are previous studies dealing with the development of FQSMS in other food commodities demonstrating their usefulness to improve food quality and safety. One of the best examples is the Food Safety Management System- diagnostic instrument (FSMS-DI), which contributes to the measurement of the performance of the FSMS in an organization suggested for edible oil or fresh produce chains (Nanyunja et al, 2015 ; Ren et al, 2016 ). Further, development of scoring systems (Stadlmüller et al, 2017 ) and best practice scores (Tzamalis et al, 2016 ) for the assessment of FQSMS are also reported.…”
Section: Introductionmentioning
confidence: 99%
“…There are previous studies dealing with the development of FQSMS in other food commodities demonstrating their usefulness to improve food quality and safety. One of the best examples is the Food Safety Management System- diagnostic instrument (FSMS-DI), which contributes to the measurement of the performance of the FSMS in an organization suggested for edible oil or fresh produce chains (Nanyunja et al, 2015 ; Ren et al, 2016 ). Further, development of scoring systems (Stadlmüller et al, 2017 ) and best practice scores (Tzamalis et al, 2016 ) for the assessment of FQSMS are also reported.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is a need to evaluate the performance of the currently implemented FSMS to identify weaknesses and suggest improvement points. Previous studies have developed different tools to evaluate the performance of FSMS (Ren et al, 2016). For example, some studies assessed FSMS using a tool of food safety management system-diagnostic instrument (FSMS-DI) for improving diagnosis (e.g.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…For example, some studies assessed FSMS using a tool of food safety management system-diagnostic instrument (FSMS-DI) for improving diagnosis (e.g. Hartwell and Edwards, 2001;Garayoa et al, 2011;Luning et al, 2013;Kirezieva et al, 2013;Ren et al, 2016). Other studies relied upon assessment tools to evaluate the microbial outputs of current FSMS (e.g.…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 2 more Smart Citations